Hedges in World University Parliamentary English Debate Championships: A Pragmatic Study - Rosaria Mita Amalia; Yusuf Hamzah (PAROLE: Journal of Linguistics and Education, 2016)
Debating is recognized as a way of doing persuasion in speech that deals with four points of debate pillars, namely: assertion, reasoning, evidence, and link back. In the last two decades, every country debater champions have gathered and involved in a high level of debate atmosphere to compete each other as their country’s representatives to have worlds’ champion title. In conjunction to the glance of debate definition, the researcher analyzed the annual world most prestigious debating championship, WUDC 2016, which took place in Thessaloniki, Greece. In this research descriptive qualitative method was used. The source of this research was taken from video streaming on Youtube showing ESL grand final round between University of Indonesia team A (Indonesia) as Prime Minister (PM) and RWTH Aachen team A (Germany) as leader of opposition (LO). The result shows that hedges are used to make the debate performance run smooth and thoroughly powerful and convincing.